2008
DOI: 10.1111/j.1471-4159.2008.05243.x
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic swelling characteristics of glial cells in the murine hippocampus, cerebellum, and retina in situ

Abstract: Glial cells are proposed to play a major role in the ionic and osmotic homeostasis in the CNS. Swelling of glial cells contributes to the development of edema in neural tissue under pathological conditions such as trauma and ischemia. In this study, we compared the osmotic swelling characteristics of murine hippocampal astrocytes, cerebellar Bergmann glial cells, and retinal Müller glial cells in acutely isolated tissue slices in response to hypoosmotic stress and pharmacological blockade of Kir channels. Hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 50 publications
(133 reference statements)
7
43
0
1
Order By: Relevance
“…In addition, marked intracellular swelling of the perivascular astroglial foot processes was present in patients who died in ALF-induced coma (Kato et al, 1992). In vitro experiments have also reported astrocyte swelling, by assessing the intracellular space using [ 3 H]-3-O-methylglucose ( Norenberg et al, 1991), or by microscopic measurements of cellular volume ( Hirrlinger et al, 2008), following the addition of pathogenic factors associated with HE. In CLD, astrocytes present a characteristic morphology, known as Alzheimer type II astrocytosis: large, swollen cells with enlarged swollen nuclei and cytoplasm, margination of chromatin, mitochondrial and rough endoplasmic reticulum proliferation and accumulation of glycogen ( Norenberg, 1977).…”
Section: Astrocyte Swelling and Brain Edema In Liver Disease/failurementioning
confidence: 98%
“…In addition, marked intracellular swelling of the perivascular astroglial foot processes was present in patients who died in ALF-induced coma (Kato et al, 1992). In vitro experiments have also reported astrocyte swelling, by assessing the intracellular space using [ 3 H]-3-O-methylglucose ( Norenberg et al, 1991), or by microscopic measurements of cellular volume ( Hirrlinger et al, 2008), following the addition of pathogenic factors associated with HE. In CLD, astrocytes present a characteristic morphology, known as Alzheimer type II astrocytosis: large, swollen cells with enlarged swollen nuclei and cytoplasm, margination of chromatin, mitochondrial and rough endoplasmic reticulum proliferation and accumulation of glycogen ( Norenberg, 1977).…”
Section: Astrocyte Swelling and Brain Edema In Liver Disease/failurementioning
confidence: 98%
“…Indeed, it has been shown that the decrease in the extracellular space volume in retinal slices superfused with glutamate is lower than expected when only the swelling of neuronal cell bodies is considered [51]. Usually, superfusion of retinal slices with a hypoosmotic solution does not induce a swelling of Müller cells for 10-15 min [25,31,57].…”
Section: Introductionmentioning
confidence: 95%
“…5). It has been shown that murine retinal glial cells maintain their cell volume constant up to 20 min of hypotonic exposure before cellular swelling becomes obvious (56). The lack of significant cellular swelling under these conditions can be explained by the activation of an endogenous purinergic signaling cascade (57).…”
Section: Gpr34-deficient Mice Show No Obvious Phenotype Under Specifimentioning
confidence: 99%